Analysis of Accessibility to Family Health Centers in Antalya Using GIS - Orhun Soydan (Turkish Journal of Agriculture: Food Science and Technology)
Family health centers in Turkey started to be implemented for the first time in Düzce in 2004 years within the scope of Law No. 5258. While determining the physical conditions of the places where family health centers are built, the first item in the regulation is that the building should be easily accessible. This situation shows the importance of the subject in terms of accessibility. While determining the features of the places where FHCs will be made, environmental characteristics are also taken into consideration. Environmental features are effective in determining the FHCs location in different ways. These impacts are divided into two groups: the physical features that pavements, roads and parks can include, and the social, cultural and institutional features of neighborhoods that include local social ties and collective activities. From this point of view, the importance of the location of family health centers relative to roads and houses is understood. The aim of this study is to examine the accessibility of Family Health Centers in Konyaaltı, Antalya, on a neighborhood basis using Geographic Information Systems. Konyaaltı has 21 Family Health Centers. As a result of the analyses, it was determined that most of the neighborhoods had problems in terms of accessibility, while a very few of them did not experience problems in terms of accessibility. In terms of the total number of buildings, the ratio of buildings that are 500 meters walking distance from any family health center by using highways is 35.56%. With these rates, 3,634 of the 10,2018 buildings remain within the limits of the regulation. Finally; suggestions were made to increase accessibility to these areas.